SOI Suspended membrane waveguide at 3.39 µm for gas sensing application - Butt, Muhammad Ali; Kazansky, Nikolai Lvovich (Photonics Letters of Poland, 2020)
In this letter, we present a numerical study on the designing of silicon-on-insulator (SOI) suspended membrane waveguide (SMW). The waveguide geometry is optimized at 3.39 µm TE-polarized light which is the absorption line of methane gas by utilizing a 3D finite element method (FEM). The transmission loss (TL) and evanescent field ratio (EFR) of the waveguide are calculated for different geometric parameters such as the width of core, the height of core and period of the cladding. We found out that TL is directly related to EFR. Therefore, a waveguide geometry can be designed which can offer high EFR at the cost of high TL or low EFR with low TL, as desired. Based on the geometric parameters used in this paper, we have obtained a TL and EFR which lies in the range of 1.54 dB-3.37 dB and 0.26-0.505, respectively. Full Text: PDF References L. Vivien et al., "High speed silicon-based optoelectronic devices on 300mm platform", 2014 16th International conference on transparent optical networks (ICTON), Graz, 2014, pp. 1-4, CrossRef Y. Zou, S. Chakravarty, "Mid-infrared silicon photonic waveguides and devices [Invited]", Photonic Research, 6(4), 254-276 (2018). CrossRef J.S. Penades et al., "Suspended SOI waveguide with sub-wavelength grating cladding for mid-infrared", Optics letters, 39(19), 5661-5664 (2014). CrossRef T. Baehr-Jones, A. Spott, R. Ilic, A. Spott, B. Penkov, W. Asher, and M. Hochberg, "Silicon-on-sapphire integrated waveguides for the mid-infrared", Opt. Express, 18(12),12127-12135 (2010). CrossRef J. Mu, R. Soref, L. C. Kimerling, and J. Michel, "Silicon-on-nitride structures for mid-infrared gap-plasmon waveguiding", Appl. Phys. Lett., 104(3), 031115 (2014). CrossRef J.S. Penades et al., "Suspended silicon waveguides for long-wave infrared wavelengths", Optics letters, 43 (4), 795-798 (2018). CrossRef J.S. Penades et al., "Suspended silicon mid-infrared waveguide devices with subwavelength grating metamaterial cladding", Optics Express, 24, (20), 22908-22916 (2016). CrossRef M.A. Butt, S.N. Khonina, N.L. Kazanskiy, "Modelling of Rib channel waveguides based on silicon-on-sapphire at 4.67 μm wavelength for evanescent field gas absorption sensor", Optik, 168, 692-697 (2018). CrossRef S.N. Khonina, N.L. Kazanskiy, M.A. Butt, "Evanescent field ratio enhancement of a modified ridge waveguide structure for methane gas sensing application", IEEE Sensors Journal CrossRef M.A. Butt, S.A. Degtyarev, S.N. Khonina, N.L. Kazanskiy, "An evanescent field absorption gas sensor at mid-IR 3.39 μm wavelength", Journal of Modern Optics, 64(18), 1892-1897 (2017). CrossRef S. Zampolli et al., "Selectivity enhancement of metal oxide gas sensors using a micromachined gas chromatographic column", Sensors and Actuators B Chemical, 105 (2), 400-406 (2005). CrossRef N. Dossi, R. Toniolo, A. Pizzariello, E. Carrilho, E. Piccin, S. Battiston, G. Bontempelli, "An electrochemical gas sensor based on paper supported room temperature ionic liquids", Lab Chip, 12 (1), 153-158 (2011). CrossRef V. Avetisov, O. Bjoroey, J. Wang, P. Geiser, K. G. Paulsen, "Hydrogen Sensor Based on Tunable Diode Laser Absorption Spectroscopy", Sensors, 19 (23), 5313 (2019). CrossRef M.A. Butt, S.N. Khonina, N.L. Kazanskiy, "Silicon on silicon dioxide slot waveguide evanescent field gas absorption sensor", Journal of Modern Optics, 65(2), 174-178 (2018). CrossRef Nikolay Lvovich Kazanskiy, Svetlana Nikolaevna Khonina, Muhammad Ali Butt, "Subwavelength Grating Double Slot Waveguide Racetrack Ring Resonator for Refractive Index Sensing Application", Sensors, 20, 3416 (2020). CrossRef H. Tai, H. Tanaka, T. Yoshino, "Fiber-optic evanescent-wave methane-gas sensor using optical absorption for the 3.392-μm line of a He–Ne laser", Opt. Lett., 12, 437-439 (1987). CrossRef M.A. Butt, S.N. Khonina, N.L. Kazanskiy, "Hybrid plasmonic waveguide-assisted Metal–Insulator–Metal ring resonator for refractive index sensing", Journal of Modern Optics, 65(9), 1135-1140 (2018). CrossRef S.A. Degtyarev, M.A. Butt, S.N. Khonina, R.V. Skidanov, "Modelling of TiO2 based slot waveguides with high optical confinement in sharp bends", 2016 International Conference on Computing, Electronic and Electrical Engineering, ICE Cube, Quetta, 2016, 10-13 CrossRef